Presence of ephedra gall midge, Ephedromyia debilopalpis Marikovskij (Diptera: Cecidomyiidae) in Iran - Omid Hadi; Hossein Lotfalizadeh; Mohammad-Hossein Kazemi; Marcela Skuhravá (Journal of Insect Biodiversity and Systematics, 2018)
We reared Ephedromyia debilopalpis Marikovskij (Dip.: Cecidomyiidae) for the fist time on Ephedra major (Ephedraceae) in the northwest of Iran in 2016. This is the new record of the genus and species for Iran. With including this new record, the known gall midge fauna of Iran reached 62 species and 34 genera.